Ultrasound-assisted leaching-dispersive solid-phase extraction followed by liquid-liquid microextraction for the determination of polybrominated diphenyl ethers in sediment samples by gas chromatography-tandem mass spectrometry - Fontana, Ariel Ramón (2010)
Ultrasound-assisted leaching-dispersive solid-phase extraction followed by dispersive liquid-liquid microextraction (USAL-DSPE-DLLME) technique has been developed as a new analytical approach for extracting, cleaning up and preconcentrating polybrominated diphenyl ethers (PBDEs) from sediment samples prior gas chromatography-tandem mass spectrometry (GC-MS/MS) analysis. In the first place, PBDEs were leached from sediment samples by using acetone. This extract was cleaned-up by DSPE using activated silica gel as sorbent material. After clean-up, PBDEs were preconcentrated by using DLLME technique. Thus, 1 mL acetone extract (disperser solvent) and 60 μL carbon tetrachloride (extraction solvent) were added to 5 mL ultrapure water and a DLLME technique was applied. Several variables that govern the proposed technique were studied and optimized. Under optimum conditions, the method detection limits (MDLs) of PBDEs calculated as three times the signal-to-noise ratio (S/N) were within the range 0.02-0.06 ng g-1. The relative standard deviations (RSDs) for five replicates were <9.8%. The calibration graphs were linear within the concentration range of 0.07-1000 ng g-1 for BDE-47, 0.09-1000 ng g-1 for BDE-100, 0.10-1000 ng g-1 for BDE-99 and 0.19-1000 ng g-1 for BDE-153 and the coefficients of estimation were ≥0.9991. Validation of the methodology was carried out by standard addition method at two concentration levels (0.25 and 1 ng g-1) and by comparing with a reference Soxhlet technique. Recovery values were ≥80%, which showed a satisfactory robustness of the analytical methodology for determination of low PBDEs concentration in sediment samples.